POSTGRADUATE EDUCATION IN KHYBER PAKHTUNKHWA - Mahmood, Khalid (Journal of Postgraduate Medical Institute, 2016)
Medical education is a continuum comprising undergraduate, postgraduate and continuing medical education. Postgraduate medical education is the phase of medical education in which doctors undertake specialized training after acquisition of their basic medical qualification. This phase of training is usually carried out according to specified regulations and rules as laid down by the concerned institute. The training is designed on the pattern of apprenticeship, meaning that the young doctors work in clinical settings with experienced colleagues and mentors who supervise their work and training.